2005
DOI: 10.1100/tsw.2005.90
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Intellectual Disability and Suicidal Behavior

Abstract: It has been assumed that impaired intellectual capacity could act as a buffer to suicidality in the population of children and adolescents with intellectual disability. The few studies that have been conducted contest this assumption, and in fact, the findings showed that the characteristics of suicidality in the population of children and adolescents with intellectual disability are very similar to other adolescents without intellectual disability. This paper reviews the few studies conducted and describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Studies have identified slightly higher IQ, co-morbid psychiatric disorders and recent psychosocial stressors as correlates of suicide risk in the ID population. Previous studies and reviews have suggested healthcare providers routinely assess for suicide risk and depression in youth with ID; 32,37 however, standardized evaluation of suicidal thoughts and behaviors is challenged by the lack of appropriate measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified slightly higher IQ, co-morbid psychiatric disorders and recent psychosocial stressors as correlates of suicide risk in the ID population. Previous studies and reviews have suggested healthcare providers routinely assess for suicide risk and depression in youth with ID; 32,37 however, standardized evaluation of suicidal thoughts and behaviors is challenged by the lack of appropriate measures.…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 175 (93%) were excluded because they focused on adults, did not specifically address SI/SB in youth with ID or focused on self-injury without intent to die. Therefore, 13 articles were identified that describe suicidal ideation and behavior in children and adolescents with ID: one comprehensive literature review, 32 three prospective studies, three chart reviews and six published case reports. For a summary of key findings from the prospective studies, chart reviews and case reports, see Tables 1, 2 and 3, respectively.…”
Section: Literature Search Strategymentioning
confidence: 99%
“…The first is the loose assumption, often made in the reporting and presentation of suicide data, that suicide rates may be similar for all those aged between 15 and 25. Some countries show a higher suicide rate for the late adolescence (20)(21)(22)(23)(24)(25) than the mid adolescence (15)(16)(17)(18)(19)(20), e.g., see Shek et al [41]. The age category 15-25 is much more heterogeneous than 15-20 and 20-25, i.e., individuals aged 15 and 20 years may behave very differently to individuals aged 21 and 24, respectively.…”
Section: Trends In Adolescent Suicidementioning
confidence: 99%
“…Viewed as an illness of the mind, suicide research has, over and above depression, followed many directions, such as a link with fatty acids [16,17], eating disorders and anorexia nervosa [18,19], persons with intellectual disability [20,21], cannabis and alcohol misuse [22,23,24,25], allergy symptoms [26], and clinical settings [24,27]; also see Shahtahmasebi [5] for more categories. Pharmacological treatment of mental illness, depression, and suicidal behaviour on its own may be controversial [28]; others suggest holistic medicine as a more effective treatment [29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…As recently as the 1980s it was widely believed that individuals with intellectual disability (ID) did not have the cognitive capacity to experience mental health problems (Smiley, 2005) and that cognitive impairment acted as a "buffer" against suicidal behaviour (Walters, et al, 1995;Merrick et al, 2005Merrick et al, , 2006. This review examines the evidence relating to suicide risk factors for individuals with ID.…”
Section: Introductionmentioning
confidence: 98%